RESILIENCE AND REINVENTION: THE JOURNEY OF MIGRANT-OWNED MICRO ENTERPRISES IN SOUTH AFRICA BEFORE, DURING, AND AFTER COVID-19 - Mutisi, Edson Chido; Mutekwe, Paddington; Padayachee, Celestine (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This paper follows foreign migrant-owned microenterprises in South Africa, tracing their paths before and after the COVID-19 pandemic. Research on micro-enterprises during the pandemic is generally inclined toward finding the impact of COVID-19 without a migration analysis. This paper bridges this gap by centering on migrant-owned businesses since they may have been affected by being owned by foreigners, a vulnerable population. The paper utilizes qualitative data to evaluate the pandemic's impact on business operations, financial security, and survival mechanisms. Furthermore, it assesses the post-pandemic revival process and locates migrant-owned small businesses' experiences in debates on migration, informality, and entrepreneurship. The primary findings of the paper illustrate that migrant-owned small businesses performed relatively well before the pandemic, with most of the owners earning above South Africa's monthly minimum wage. The paper also discovered that many foreign-owned small enterprises were impacted by a decline in demand during the lockdown, resulting in a loss of revenue, while some have struggled to recover post-COVID-19. Keywords: South Africa; COVID-19; Small Businesses; Migrants; Micro-Enterprises